THE MEANING OF THE WORD “QAWWAMUN”: SEMIOTIC ANLYSIS OF JULIA KRISTEVA’S INTERTEXTUALITY IN TAFSIR AL-MIZAN AND TAFSIR AL-MISHBAH - Arif, Muhammad Syaikhul; Uswatun Chasanah, Alifatul Lusiana; Kamal, Jawahir (UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract Nowadays, women leadership has become a much-discussed topic. However, in practice, it still leaves many gaps that need to be continuously improved and applied on a large scale. Society's restrictive perspective on leadership, which insists that it must be carried out by men, is a product of centuries of indoctrination by patriarchal culture, continually reproduced by various groups, including religious authorities. Islamic legal products are the result of interpretations of Quranic verses, so if bias exists in the interpretation process, biases will also manifest in legal products and the general understanding of society. To gain a new perspective in understanding leadership, this research aims to explore the shift in the meaning of 'qawwamun' by examining the viewpoints of two Quranic commentators whose works are interconnected but produce two different perspectives, allowing us to conclude that there has been a change in their ideological stance Keywords: Women Leadership, Semiotic, Intertextuality. Abstrak Dewasa ini kepemimpinan perempuan telah menjadi sebuah topik yang banyak dibicarakan, namun pada taraf praksisnya, ia masih menyisakan amat banyak celah-celah untuk terus diperbaiki dan diterapkan secara masif. Keterkungkungan cara pandang masyarakat atas kepemimpinan dengan mengharuskan penerapannya dilaksanakan oleh lelaki, merupakan buah dari doktrinasi berabad abad oleh budaya patriarki, yang terus direproduksi oleh berbagai macam kalangan, dan tak luput dari kalangan otoritatif keagamaan. Produk hukum dalam agama Islam merupakan buah dari penafsiran atas ayat-ayat Alquran, maka apabila sudah terdapat bias sejak dalam upaya menafsirkan ayat, maka akan lahir pula bias-bias pada produk hukum dan pola pemahaman masyarakat umum. Guna mendapat sudut pandang baru dalam memaknai pemimpin, maka dalam penelitian ini akan diupayakan untuk mencari pergeseran makna qawwamun dengan melihat sudut pandang dua orang mufassir yang karya tafsirnya saling berkaitan, namun memunculkan dua sudut pandang yang berbeda, serta dapat ditarik kesimpulan telah terdapat ideologem yang berubah dari keduanya. Kata Kunci: Kepemimpinan Perempuan, Semiotik, Intertekstualitas.